2020
DOI: 10.1108/mi-04-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

The interfacial reliability of through-glass vias for 2.5D integrated circuits

Abstract: Purpose Glass is a promising interposer substrate for 2.5 D integration; yet detailed analysis of the interfacial reliability of through-glass vias (TGVs) has been lacking. The purpose of this paper is to investigate the design and material factors responsible for the interfacial delamination in TGVs and identify methods to improve reliability. Design/methodology/approach The interfacial reliability of TGVs is studied both analytically and numerically. An analytical solution is presented to show the dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Cracks were generated by the existence of radial stress ( ) and shear stress ( ) at the TGV–Cu interface in the preliminary theoretical and FE model investigation [ 12 , 13 , 14 ]. The elastic-plastic yield criterion was used in the analysis.…”
Section: Effect Of Geometric Parameters and Materials On Wafer Reliab...mentioning
confidence: 99%
“…Cracks were generated by the existence of radial stress ( ) and shear stress ( ) at the TGV–Cu interface in the preliminary theoretical and FE model investigation [ 12 , 13 , 14 ]. The elastic-plastic yield criterion was used in the analysis.…”
Section: Effect Of Geometric Parameters and Materials On Wafer Reliab...mentioning
confidence: 99%
“…In addition, the failure mechanism and optimization rule of TGV interposer architecture were systemically investigated [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Tensile radial and circumferential stresses were attributed to the origin of the circumferential cracks and the formation of radial cracks, respectively [ 11 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different layout designs, such as fully filled via and conformal via, were demonstrated and investigated in terms of their thermomechanical reliability [ 17 ]. Interfacial delamination between glass interposers and Cu-filled TGV was explored, and the corresponding energy release rate was proportional to the via diameter and the thermal mismatch strain, which was highly dependent on the layout design parameters [ 18 ]. A metallization process filled with Ag-paste composite solution was presented, and its effectiveness was compared with that of the general Cu electroplating process; the analytical results revealed that the aforementioned metallization process would introduce different cracking behaviors [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce Cu protrusion-induced stress, a conformal-type TGV has been demonstrated, and a fully-filled TGV with considerable copper protrusion during thermal cycling was revealed [ 16 ]. The interfacial energy release rate of the interface between Cu-filled TGV and different glass materials has been investigated through the finite element analysis (FEA) simulation and analytical model [ 17 ]. For different filling materials of TGV, the crack formation mechanism can differ considerably; moreover, radial-type and circumferential-type cracks were found in electroplated Cu-filled TGV and sliver-paste-filled TGV during the heating process in [ 18 ].…”
Section: Introductionmentioning
confidence: 99%